Application of the Inverse Chronopotentiometry Method to Control the Content of Toxic Elements in Refining Production - Melnyk, Oksana; Galimova, V.; Radzievska, Irina; Marynin, Andriy (My University, 2021)
Ukraine is one of the world leading exporters of sunflower oil. An important safety indicator is the content of toxic elements in it, which should not exceed the maximum permissible concentrations. Toxic elements entering the human body reduce the functions of individual systems and organs and lead to immunodeficiency. The toxic elements by which food products are controlled include copper (Cu), zinc (Zn), iron (Fe), cadmium (Cd), lead (Pb), arsenic (As), and mercury (Hg).
Keywords: sanflower oil; production stages; toxic elements; inversion and chronopotentiometry; соняшникова олія; стадії виробництва; токсичні елементи; інверсія та хронопотенціометрія; кафедра технологічного обладнання та комп’ютерних технологій проектування; кафедра експертизи харчових продуктів; кафедра технології жирів, хімічних технологій харчових добавок та косметичних засобів